Transcarotid versus transaxillary access for transcatheter aortic valve replacement with a self-expanding valve: A propensity-matched analysisCentral MessagePerspective - Keith B. Allen, MD; Daniel Watson, MD; Amit N. Vora, MD; Paul Mahoney, MD; Adnan K. Chhatriwalla, MD; Jonathan G. Schwartz, MD; Antoine Keller, MD; Nishtha Sodhi, MD; Daniel Haugan, MS; Michael Caskey, MD (JTCVS Techniques)
Transaxillary access has been the most frequently used nonfemoral access route for transcatheter aortic valve replacement (TAVR) with a self-expanding valve. Use of transcarotid TAVR is increasing; however, comparative data on these methods are limited. We compared outcomes following transcarotid or transaxillary TAVR with a self-expanding, supra-annular valve. Methods: The Transcatheter Valve Therapy Registry was queried for TAVR procedures using transaxillary and transcarotid access between July 2015 and June 2021. Patients received a self-expanding Evolut R, PRO, or PRO + valve (Medtronic) and had 1-year follow-up. Thirty-day and 1-year outcomes were compared in transcarotid and transaxillary groups after 1:2 propensity score-matching. Multivariable regression models were fitted to identify predictors of key end points. Results: The propensity score–matched cohort included 576 patients receiving transcarotid and 1142 receiving transaxillary access. Median procedure time (99 vs 118 minutes; P < .001) and hospital stay (2 vs 3 days; P < .001) were shorter with transcarotid versus transaxillary access. At 30 days, patients with transcarotid access had similar mortality (Kaplan–Meier estimates 3.7% vs 4.3%, P = .57) but significantly lower stroke (3.1% vs 5.9%; P = .017) and mortality or stroke (6.0% vs 8.9%; P = .033) compared with patients receiving transaxillary access. Similar differences were observed at 1 year. Transaxillary access was associated with increased risk of 30-day stroke (hazard ratio, 2.14; 95% confidence interval, 1.27-3.58) by multivariable regression analysis. Conclusions: Transcarotid versus transaxillary access for TAVR using a self-expanding valve is associated with procedural benefits and significantly lower stroke and mortality or stroke at 30 days. In patients with unsuitable femoral anatomy, transcarotid access may be the preferred delivery route for self-expanding valves.